Extraction of Glucose from Colocasia esculenta Starch: A Major Substrate for Ethanol Production - Mohanty, Chirasmita; Das, Pratyush Kumar; Purohit, Gopal Krishna; Pattanaik, Sangram; Palo, Swadhin (International Journal of Scientific Research in Biological Sciences, 2021)
Global energy consumption and demand are on an ever-rising trend. The current situation has led to an increased dependence on fossil fuels, thereby leading to dwindling fuel reserves, a rise in fuel prices, and several environmental problems. To alleviate the current pressure on conventional fuel sources researchers have started to shift their focus onto new renewable options like biofuels. Global mandates of blending bio-ethanol with petroleum have been accepted differentially in different countries. The global biofuel market is expected to rise in the coming years and pose huge opportunities for researchers as well as stakeholders. Starch is a major substrate for the production of glucose which in turn acts as a primary substrate for the production of ethanol. The current work emphasizes the use of Colocasia esculenta (Taro) starch for the production of glucose which could be further used for biofuel production. The glucose was produced from taro starch by acid hydrolysis using hydrochloric acid as the hydrolyser. Process parameters like acid concentration, temperature, and time of incubation were optimized. At an optimum acid concentration of 5%, the temperature of 100°C, and incubation time of 20 minutes, 25.3 mg of glucose per gram of starch (2.53%) was produced. The glucose yield was found to be comparatively higher as compared to other starchy plants reported. Keeping in mind the wide availability of the plant, and the ability to grow in wide conditions, it could be used as a potential source for the production of bioethanol.